An Update on the Implications of New Psychoactive Substances in Public Health - Simão, Ana Y. (2022)
Funding: The Associate Laboratory Institute for Health and Bioeconomy–i4HB (project LA/P/0140/2020) which are financed by National Funds from FCT/MCTES. Ana Y. Simão and Mónica Antunes acknowledge the PhD fellowships from FCT (2020.05765.BD). Publisher Copyright: © 2022 by the authors. Licensee MDPI, Basel, Switzerland.